A basic bottom-up approach for small systems ofsafe-water supply: a decentralized case study in Uganda - Andreolli, Marco; Giovannini, Mattia; Fatone, Francesco; Kyamunyogonya, Magdalen; Yatuha, Jane (Journal of Water Supply: Research and Technology, 2015)
In developing countries, diarrhea is known as the major cause of burden among children. Diarrhea is associated to poor quality of drinking water, inadequate sanitation and insufficient hygiene behavior. This work introduces a bottom-up approach for the implementation of a borehole installation in conjunction with proper water handling in rural areas. A pre-intervention survey was performed as a basic decision tool, and a post-intervention survey was performed to evaluate the quality of the intervention. In particular, information was collected regarding the water source, the health status, the water related behavior, hygiene and on other issues. Furthermore, coliforms and fecal contamination of the water sources used during the dry season were determined. Prior to the intervention the monthly diarrhea incidence was estimated to be around 22.0% among children. Microbiological analysis showed that sources of water (river, swamp and waterhole) presented a high fecal contamination (>250 for river and swamp, 110 most probable number index 100 mL–1for waterhole).After the intervention, the monthly diarrhea incidence dropped to 10.2% among children, showing a significant reduction of 11.8% (p<0.01). Even though this represents an exciting result, more intervention projects at household level are required in order to further reduce the diarrhea incidence..
Keywords: Borehole; Bottom-up approach; Developing countries; Diarrhea; Drinking water; Questioner; Water contamination